Implementation of Problem-Based Learning to Improve Students’ Learning Outcomes in Waves: A Case of MAN Balikpapan - Amin, Bunga Dara; Rahmawati, Rahmawati; Haris, Abdul (Jurnal Pendidikan MIPA, 2022)
This research is a pre-experimental research that aims to determine the physical learning outcomes of students at MAN Balikpapan who are taught using problem based learning. The independent variable in this study is problem based-learning and the variable is the student’s physics learning outcomes on the subject matter of sound waves. The research subject is class XI MIPA 1 MAN Balikpapan which has 33 participants The research data by giving a test of learning outcomes on the subject matter of the wave in the form of a posttest. The data analysis technique is descriptive analysis in the form of the average score of learning outcomes, standard deviation and variance. Based on descriptive analysis, the average score of learning result in class XI MIPA 1 is 82,97. It can be said that the physical learning result of students who are taught using problem based-learning are in the very high category. Keywords: problem based learning, learning outcomes, waves concept. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1358-1366